Rheumatoid Synovial Fluids Regulate the Immunomodulatory Potential of Adipose-Derived Mesenchymal Stem Cells Through a TNF/NF-κB-Dependent Mechanism - Sayegh, Souraya; El Atat, Oula; Diallo, Katy; Rauwel, Benjamin; Degboé, Yannick; Cavaignac, Etienne; Constantin, Arnaud; Cantagrel, Alain; Trak-Smayra, Viviane; Alaaeddine, Nada; Davignon, Jean-Luc (Frontiers in Immunology, 2019)
Introduction: Adipose-derived mesenchymal stem cells (ADSC) have been shown to have remarkable immune-modulating effects. However, their efficacy in clinical trials has yet to be fully demonstrated. This could be due to a lack of a proper inflammatory environment in vivo that primes ADSC. Here, we define how the articular microenvironment of rheumatoid arthritis (RA) patients modulates the therapeutic efficiency of ADSC. Methods: Synovial fluids (SF) were collected from 8 RA patients, 2 Spondyloarthritis patients and one control synovial fluid from a patient undergoing traumatic-related surgery. SF inflammatory status was determined by routine analysis and quantification of pro-inflammatory cytokines. ADSC were first treated with SF and ADSC proliferation and gene expression of immunomodulatory factors was evaluated. In order to determine the mechanisms underlying the effect of SF on ADSC, tumor necrosis factor (TNF), interleukin-6 (IL-6) and NF-κB neutralization assays were performed. To evaluate the effect of SF on ADSC functions, ADSC were pre-treated with SF and then co-cultured with either macrophages or T cells. The modulation of their phenotype was assessed by flow cytometry. Results: Pro-inflammatory RASF maintained the proliferative capacity of ADSC and upregulated the gene expression of cyclooxygenase-2 (COX2), indoleamine-1,2-dioxygenase (IDO), interleukin-6 (IL-6), tumor-necrosis factor stimulated gene 6 (TSG6), intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1) and programmed death-ligand 1 (PD-L1), all factors involved in ADSC immunomodulatory potential. The RASF-induced gene expression was mainly mediated by TNF alone or in combination with IL-6 and signaled through the NF-κB pathway. Conditioning ADSC with pro-inflammatory RASF enhanced their ability to induce CD4+Foxp3+CD25high regulatory T cells (Tregs) and inhibit pro-inflammatory markers CD40 and CD80 on activated macrophages. Conclusions: Inflammatory synovial fluids from RA patients had the capacity to modulate ADSC response, to induce Tregs and modulate the phenotype of macrophages. The clinical use of ADSC in affected joints should take into account the influence of the local articular environment on their potential. Having a sufficient pro-inflammatory microenvironment will determine whether optimal immunoregulatory response should be expected. Direct ADSC intra-articular delivery to patients could be a potential strategy to properly prime their immunomodulatory potential and enhance their clinical benefits.